2008
DOI: 10.1590/s0100-204x2008000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional e produção de laranjeira 'Pêra' em função da vegetação intercalar e cobertura morta

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da cobertura morta e da vegetação intercalar composta por gramíneas e leguminosas perenes nas propriedades químicas do solo e no estado nutricional de plantas de laranjeira 'Pêra' (Citrus sinensis (L.) Osbeck) enxertada em limoeiro 'Cravo' (Citrus limonia Osbeck). Os tratamentos testados foram: T1, Brachiaria ruziziensis R. Germ. & Evrard na entrelinha sem cobertura morta na linha; T2, B. ruziziensis na entrelinha e cobertura morta na linha; T3, B. ruziz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
5
0
3
Order By: Relevance
“…Faber et al (2001) found that root system growth in the superficial soil layers can be favored by the presence of mulching, facilitating the absorption of nutrients such as phosphorus, which is accumulated in the superficial layers due to its low mobility. In addition , Bremer Neto et al (2008) stated that the balance between mineralization and immobilization of soil N could be affected by mulching distribution in order to reduce its availability to plants and require complementary fertilization of this nutrient.…”
Section: Resultsmentioning
confidence: 99%
“…Faber et al (2001) found that root system growth in the superficial soil layers can be favored by the presence of mulching, facilitating the absorption of nutrients such as phosphorus, which is accumulated in the superficial layers due to its low mobility. In addition , Bremer Neto et al (2008) stated that the balance between mineralization and immobilization of soil N could be affected by mulching distribution in order to reduce its availability to plants and require complementary fertilization of this nutrient.…”
Section: Resultsmentioning
confidence: 99%
“…No caso do consórcio com fruteiras as leguminosas herbáceas perenes se mostram bastante promissoras (Bremer Neto et al, 2008) pelo fato de serem mantidas como coberturas vivas por meio de roçadas periódicas, após semeio, dispensando nova compra de sementes ou mudas em ciclos posteriores da cultura principal. Para a bananeira resultados de pesquisas têm demonstrado boa eficiência das plantas de cobertura no que diz respeito ao fornecimento do N (Espíndola et al, 2006b;Perin et al, 2009) mas muito ainda se precisa saber sobremaneira no que diz respeito à escolha das melhores plantas de cobertura e do manejo desse sistema sob irrigação em regiões semiáridas.…”
Section: Introductionunclassified
“…Alternatively, there is the possibility of producing grass biomass between the rows of orange orchards with mechanical mowing for mulch accumulation on the soil in plant rows (Beraldo et al 2007;Bremer Neto et al, 2008;Fidalski et al, 2009). However, the effect of mulching in the plant rows has not been evaluated for the possible responses of rootstocks, which may differ in soil water uptake and consumption.…”
Section: Introductionmentioning
confidence: 99%